Case Report: A novel heterozygous nonsense mutation in KRIT1 cause hereditary cerebral cavernous malformation - Liu, Zhenxing; Guo, Kaikai; Hu, Xuebin; Zhang, Xianqin (Frontiers in Oncology, 2023)
Cerebral cavernous malformation (CCM) is a vascular malformation of the central nervous system and mainly characterized by enlarged capillary cavities without intervening brain parenchyma. Genetic studies have identified three disease-causing genes (CCM1/KRIT1, CCM2/MGC4607 and CCM3/PDCD10) responsible for CCM. Here, we characterized a four-generation family diagnosed with CCM and identified a novel heterozygous mutation c.1159C>T, p.Q387X in KRIT1 gene by whole exome sequencing and Sanger sequencing. The Q387X mutation resulted in premature termination of KRIT1 protein, which was predicted to be deleterious by the ACMG/AMP 2015 guideline. Our results provide novel genetic evidence support that KRIT1 mutations cause CCM, and are helpful to the treatment and genetic diagnosis of CCM.